Logarithmic barrier-augmented Lagrangian function to the optimal power flow problem - Baptista, E. C.; Belati, E. A.; da Costa, GRM (Elsevier B.V., 2005)
This paper presents a new approach to solve the Optimal Power Flow problem. This approach considers the application of logarithmic barrier method to voltage magnitude and tap-changing transformer variables and the other constraints are treated by augmented Lagrangian method. Numerical test results are presented, showing the effective performance of this algorithm. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: primal-dual logarithmic barrier; optimization methods; reactive dispatch; nonlinear programming